The characterization and modelling of antipredator defensive behavior - Blanchard, R J; Blanchard, D C; Rodgers, J; Weiss, S M (Neuroscience and biobehavioral reviews, 1990)
The mammalian behavioral antipredator defense systems have been characterized in terms of reactions to present, localizable, threat stimuli: Analysis of the relationship between features of the predator and the environment, and specific defensive behaviors indicates that the latter can be predicted with a high degree of accuracy. A different set of defensive behaviors are seen when rats living in burrow systems are confronted by a predator outside the burrow. Flight to the burrow and immobility inside the burrow are followed by active investigation of the surface where the cat was seen (risk assessment), with all of these accompanied by inhibition of nondefensive behaviors such as eating, drinking, sexual behavior and aggression. Two additional behaviors are described in this context, ultrasonic cries made at a high initial rate (50% time) by animals inside the burrow systems, and declining over 1-2 hours following predator exposure, and, a specific modification of eating patterns when the subjects return to the surface and begin to eat. Eating bouts are shortened, with fewer episodes of continuous eating, interspersed with intervals of scanning of the environment, a vigilance activity previously reported in field research. This analysis of a broad spectrum of defensive behaviors is being used to develop test batteries providing simplified models of these phenomena.